(untitled) (Research, Society and Development, 2023)
Introduction: Poliomyelitis is a viral disease caused by the poliovirus, whose infection results mainly in neuromotor problems that can be prevented through immunization. The disease was considered eradicated around the world thanks to intense vaccination campaigns, however, in recent years, an increase in these cases has been observed, especially in Brazil, indicating an inefficiency in the fight against the disease. Objective: Therefore, this article aims to investigate the national rates of vaccination coverage against poliomyelitis recorded in recent years and discuss their main reasons. Methodology: A qualitative-quantitative bibliographical review was carried out, where a survey of bibliographic data was carried out on the ScieLo and PubMed platforms and a survey of data regarding polio vaccine coverage on the DataSUS platform. Articles in English and Portuguese, published between 2012 and 2022, were selected. Results: In the early 2010s, vaccination coverage against poliomyelitis was 100%, however, from 2015 this value began to progressively decrease, until it reached unsatisfactory levels. rates of 76% in 2020 and 69% in 2021. This phenomenon has also been observed with other vaccine-preventable diseases, therefore, it is stipulated that denial of science, vaccine refusal and the dissemination of fake news are the main causes of this problem, even more so considering that the recent COVID-19 pandemic has intensified all these factors. Conclusion: It is concluded that immunization against poliomyelitis is decreasing, as a result of several factors and for this reason, it signals a possible return of the infection as a public health problem repeatedly.